โครงการการออกแบบยาตามโครงสร้างสำหรับสารต้านโรคมาลาเรีย ในฐานะสารยับยั้งเอนไซม์ไดไฮโครโฟเลทรีดักเทส : รายงานวิจัยฉบับสมบูรณ์ - พรเทพ สมพรพิสุทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
Understanding the structural basis of protein-ligand complex will help to design an efficient drug against malaria disease. Particularly, the resistance to antifolate drugs is due to the mutation of the malarial enzyme. This research presents the results of designing inhibitors for malarial dihydrofolate reductase from Plasmodium falciparum (PfDHFR) by means of structure-based drug design. The three-dimension structure of PfDHFR was constructed using sequence alignment and x-ray structures of dihydrofolate reductase from other species as the structural template. Structures of the malaria inhibitors, pyrimethamine (PYR) and cycloguanil (CYC), were built and then docked into the PfDHFR’s binding site by adopting similar orientation to the DHFR’s substrate or the inhibitors from x-ray structural data of the DHFR complexes. Molecular dynamics calculation was performed to simulate the enzyme in solution and to study the structure, dynamics, and the stability of the enzyme-drug interactions. On the basis of identifying possible interactions with amino acids in the enzyme binding sites, PYR’s and CYC’s derivatives were designed. In the screening process, and inhibitor will be eliminated from the designed list if the interacting score is below the cutoff or the derivative is as same as that designed from Human DHFR. The homology model of PfDHFR provided an insight into the molecular basis of drug binding to the enzyme. The model can be used to describe the cause of drug resistance to some PfDHFR mutants. A comparison between the model and recent x-ray data of PfDHFR showed that both structures were considerably similar. Fragment-search analysis gave a total of seven derivatives, of which only one, phenylpropyl substituent, can be experimentally examined. The inhibition constant of this derivative complexed to the wildtype enzyme was similar to that of pyrimethamine. Inhibitor design using the x-ray data of PfDHFR is currently in progress.